Functional Coordination Polymers and Metal–Organic Frameworks (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of contributions on the synthesis, characterization, and applications of Metal-Organic Frameworks (MOF) and Coordination Polymers (CP). Coordination Polymers (CP) and Metal–Organic Frameworks (MOF) are at the core of contemporary research on inorganic materials. The virtually infinite combination of their building blocks—inorganic metallic nodes (single ions or clusters) and organic polytopic linkers (polycarboxylates, bridging N-/S-/O-containing heterocycles)—generates solid air- and water-stable compounds. Interesting features from an applicative point of view are porosity, large surface area, and lattice flexibility (the “breathing” effect). These properties make them ubiquitous in several fields of materials science: gas storage and separation, luminescent sensing, heterogeneous catalysis, and magnetism.